The impact of ansiogenic factors in patients with Temporomandibular Disorders (TMD) attended at the Dental Clinic of the University of the Amazon State during the New Coronavirus (COVID-19) Pandemic (Research, Society and Development, 2022)
The pandemic generated a state of calamity and social panic at a global level, intensifying levels of stress and anxiety, causing people to suffer psychological and social impacts to different degrees. Furthermore, it directly affected patients with orofacial pain, bruxism and Temporomandibular Disorders, since they are influenced by the emotional state of being. The present study aimed to study the impact of anxiogenic factors in patients with TMD treated at PoliUEA during the COVID-19 pandemic. This is an analytical, observational cross-sectional study with a qualitative approach to be quantified. Thus, a questionnaire based on the DC/TMD was used for data collection. A sample of 83 patients was obtained, being: 74 (89.1%) women and 9 (10.9%) men and a prevalent age group between 18 and 59 years (96.4%). 54.2% of patients reported having various concerns while 63.9% reported feeling nervous and/or anxious. 88% indicated aggravation of pain during the period of social isolation, while 12% reported no significant change in terms of worsening pain symptoms. Based on the results, it was concluded that there is a relationship between the worsening of symptoms in patients with TMD treated at the PoliUEA caused by social isolation during the COVID-19 pandemic and the use of methods - such as DC/TMD - is recommended, since they encompass the biopsychosocial assessment of the patient and there are indicators of such an impact on the individual's pain.